1973
DOI: 10.1901/jaba.1973.6-383
|View full text |Cite
|
Sign up to set email alerts
|

REWARDING PSYCHIATRIC AIDES FOR THE BEHAVIORAL IMPROVEMENT OF ASSIGNED PATIENTS1

Abstract: Different ways of modifying the aide-patient relationship to promote improvement in psychiatric patients were investigated. Psychiatric aides were given information about the behavior of assigned patients, cash awards based on the improvement of assigned patients, and different kinds of supervision by the psychology staff; the effects of these variables on a large number of psychiatrically relevant behaviors were measured. Appropriate behavior of patients increased when the aides were given quantitative inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…One technique that has been successful in producing changes in other areas is public posting of performance. For example, public posting has been successfully used to improve the performance of psychiatric aides and attendants (Panyan, Boozer, & Morris, 1970;Pomerleau, Bobrove, & Smith, 1973;Quilitch, 1975), swimmers (McKenzie & Rushall, 1974), tutors (Barnard, Christophersen, & Wolf, 1974), and elementary school children (Van Houten, Hill, & Parsons, 1975;Van Houten, Morrison, Jarvis, & McDonald, 1974;Van Houten & Van Houten, 1977). The purpose of the present experiment is to determine whether public posting of driver performance can reduce speeding in a residential area.…”
mentioning
confidence: 99%
“…One technique that has been successful in producing changes in other areas is public posting of performance. For example, public posting has been successfully used to improve the performance of psychiatric aides and attendants (Panyan, Boozer, & Morris, 1970;Pomerleau, Bobrove, & Smith, 1973;Quilitch, 1975), swimmers (McKenzie & Rushall, 1974), tutors (Barnard, Christophersen, & Wolf, 1974), and elementary school children (Van Houten, Hill, & Parsons, 1975;Van Houten, Morrison, Jarvis, & McDonald, 1974;Van Houten & Van Houten, 1977). The purpose of the present experiment is to determine whether public posting of driver performance can reduce speeding in a residential area.…”
mentioning
confidence: 99%
“…In Experiment I it was found that a brief demonstration of how to teach an autistic child new behaviors was sufficient to teach parents how to teach those children those behaviors. However (Gardner, 1972;Hall, 1972;Katz, Johnson, and Gelfand, 1972;Paul, McInnis, and Mariotto, 1973); the use of verbal or written feedback (Cooper, Thomson, and Baer, 1970;Cossairt, Hall, and Hopkins, 1973; Gage 1963; Panyon, Boozer, and Morris, 1970;McNamara, 1971); the use of social reinforcement (Brown, Montgomery, and Barclay, 1969;McDonald, 1973); the use of token reinforcement (Breyer and Allen, Note 1; Bricker, Morgan, and Grabowski, 1972;Katz et al, 1972;McNamara, 1971;Pomerleau, Bobrove, and Smith, 1973); and the use of modelling procedures (Engelin, Knutson, Laughy, and Garlington, 1968;Ringer, 1973 (SPRING 1978(SPRING ) 1978 …”
mentioning
confidence: 99%
“…To assure employee performance in conducting these effective training programs in large institutions, special employee motivation methods have been required as noted in one of the earliest descriptions of an institutional program in which the employees were given job privileges as reinforcement for meeting the standards of employee performance (Ayllon & Azrin, 1968). Systematic studies have since been conducted showing that employee absenteeism can be reduced (Stephens & Burroughs, 1978;Pedalino & Gamboa, 1974;Shoemaker & Reid, 1980), job performance increased (Pommer & Streedbeck, 1974;Patterson, Griffin, & Panyan, 1976;Hollander & Plutchik, 1972) and staff-patient interaction increased (Iwata, Bailey, Brown, Foshee & Aldern, 1976;Buel & Born, 1977;Pomerleau, Bobrove, & Smith, 1973).…”
Section: Introductionmentioning
confidence: 99%